2018
DOI: 10.2134/jeq2017.09.0385
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Filled Porosity as a Key to Reducing Dissolved Arsenic and Cadmium Concentrations in Paddy Soils

Abstract: Simultaneous suppression of rice ( L.) uptake of As and Cd is challenging because these toxic elements are immobilized under contrasting redox conditions. Given the notion that oxygen diffusion governs redox conditions in temporarily drained paddy soil, we assume that the key to simultaneous suppression of dissolved As and Cd concentrations is air-filled porosity (AFP) of soil. The objectives of this study were to reveal relationships between AFP and dissolved As and Cd concentrations in paddy soils and to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…These values are close to the ones previously reported with 0.048 ± 0.008 for ε Pt reaction and 0.085 ± 0.007 cm 3 cm À3 for ε Pt aeration from the same study site (Dorau et al, 2018). Besides the overall linkage between ε and E H , Nakamura et al (2018) demonstrated the benefit from these kind of pedotransfer functions to water management practices, for example, when ε is known but data about reduced and toxic species in soil solution is missing. They found that dissolved arsenic (As) was only appreciable when ε was smaller 0.04-0.06 cm 3 cm À3 at a plot that featured a similar particle size distribution compared with our study.…”
Section: Soil Aeration Assessed Via Tensiometric Readingssupporting
confidence: 87%
See 1 more Smart Citation
“…These values are close to the ones previously reported with 0.048 ± 0.008 for ε Pt reaction and 0.085 ± 0.007 cm 3 cm À3 for ε Pt aeration from the same study site (Dorau et al, 2018). Besides the overall linkage between ε and E H , Nakamura et al (2018) demonstrated the benefit from these kind of pedotransfer functions to water management practices, for example, when ε is known but data about reduced and toxic species in soil solution is missing. They found that dissolved arsenic (As) was only appreciable when ε was smaller 0.04-0.06 cm 3 cm À3 at a plot that featured a similar particle size distribution compared with our study.…”
Section: Soil Aeration Assessed Via Tensiometric Readingssupporting
confidence: 87%
“…In another study, root elongation rate of radiata pine seedlings was close to zero at ε < 0.05 cm 3 cm À3 , a finding that was independent of soil texture (Zou et al, 2001). This indicates that a similar tipping range in ε indicated the transition from reducing towards oxidising soil conditions since As was rapidly immobilised (Nakamura et al, 2018) and root elongation was enhanced by invading O 2 above the ε threshold (Zou et al, 2001).…”
Section: Soil Aeration Assessed Via Tensiometric Readingsmentioning
confidence: 96%